Mutations in 23S rRNA gene associated with clarithromycin resistance in Helicobacter pylori clinical isolates from Saint-Petersburg - Starkova D.A.; Gladyshev N.S.; Polev D.E.; Egorova S.A.; Svarval A.V. (Клиническая микробиология и антимикробная химиотерапия)
Objective.